The effect of nonlinear pedagogical principles on herding behaviour in a modified football game - Lee, Wei Jie (2016)
The interactions of mass individuals in social, neurobiological systems such as bird flocks and fish schools provide countless examples of spontaneous pattern formation. A commonly observed behavioural pattern that stifles the collective gameplay of young children in team sports is the herding phenomenon. Nonlinear Pedagogy (NP) has been proposed as a suitable approach for altering such behaviour. The purpose of this study was to determine the effectiveness of an NP approach in reducing herding behaviour in a modified football for young male children. It is hypothesised that the NP interventions would lead to an increased mean SI and TC distance in a modified football game. Sixteen male novice participants aged 9 to 10 years, were randomly allocated to the NP and control (CON) group and tasked to play a 4v4 modified football. The NP group was subjected to two blocks of interventions underpinned by NP principles. The variables, Stretch Index (SI) and Team Centres (TC) distance were obtained by tracking the positional data of the players. Two separate 2 (group) x 3 (time) Mixed Factorial ANOVA analyses were performed on the variables. The results revealed that the NP group exhibited a significant increase in mean SI and higher effect size (ηp2= 0.17) whereas a significant reduction was observed for CON. Although a significant decrease of TC distance was observed for the NP group, it is proposed that the variable may not be appropriate for investigating herding behaviour. The results suggest that NP is effective in reducing herding behaviour in children.